Preliminary study of antimicrobial (AM) effects of starch-based film incorporated with nisin, lysozymes and lauric acid - Khairuddin, Nozieana; Muhamad, Ida Idayu (2005)
Active Packaging (AP) concept is a current trend in food packaging industries. An antimicrobial (AM) Active Packaging can be made by incorporating and immobilizing suitable AM agents into food packages and applying a bio switch concept. By that, the mechanism of antimicrobial release between the developed bio-switch particles and the stimulus of a microbial contamination can be studied. A starch-based film was prepared and incorporated with antimicrobial agents, i.e. nisin, lysozyme and lauric acid. This film was then inoculated with the bacteria Escherichia Coli to carry out the microbial contamination study. The inhibition of E. Coli by the AM film was clearly observed in the broth and culture agar test. The decreased of optical density (OD 600nm) showed the inhibition of E. Coli growth. While, the clear zones formed on the film appearance showed that AM agents give good inhibition to the growth of E. Coli with satisfying inhibition rate. Lysozyme-incorporated film shows better inhibition than the other two in both tests.